2-[(4-Formylphenyl)(hydroxy)methyl]acrylonitrile - Prasanna, C. M. Sai (International Union of Crystallography, 2011)
In the title compound, C(11)H(9)NO(2), the mean planes formed by the phenyl and acryl group are almost orthogonal to each other, with a dihedral angle of 88.61 (7)°. The carbonitrile side chain is almost linear, the C—C—N angle being 179.54 (16)°. In the crystal, molecules are linked by intermolecular O—H⋯O interactions into infinite chains running parallel to the b axis.